Modulated fluorescence detection with microelectromagnetic traps. Issue 6 (27th February 2015) - Zakeri, Rashid; Basore, Joseph R.; Baker, Lane A.
Abstract : Modulation of magnetic fields in microelectromagnetic traps (METs) is used to enhance signal to noise gains for quantification of magnetic particles captured from a microfluidic analyte stream. Abstract : Microelectromagnetic traps (METs) were utilized to concentrate streptavidin modified magnetic particles from a microfluidic analyte stream. Particle capture was detected by bioconjugation either to biotinylated quantum dots or to DNA hybrids labeled with biotin and fluorescein. Subsequent modulation of the MET trapping field resulted in modulated fluorescence intensity at the MET. Detection of pM concentrations of streptavidin bound to magnetic particles and fM concentrations of DNA was possible through Fourier analysis of the modulated fluorescence response. This detection strategy represents a suitable approach to signal enhancement for magnetic pull-down assays and related technologies.